COMPARING TRANSLATION PRODUCED BY GOOGLE TRANSLATION TOOL TO TRANSLATION PRODUCED BY TRANSLATOR - Dyah Purwaningsih (Journal of English Language Studies, 2016)
Translation, as defined by many scholars, is a message-transferring process from one language or source language (SL) into another language or target language (TL). Thus, it refers to the process that a translator does in conveying the messages which is also called a decision-making process. It means a translator must decide the words s/he is going to use in translation activity, because a word might have more than one equivalents; one word might represent more than one meaning.  To produce an accurate, acceptable, and readable translation, a translator must have one of translation competences called transfer competence. This competence cannot be fulfilled by translation machine like Google translation and any other translation tools because a machine does not have linguistic sense as  translators do. However, along with the development of information technology, people are spoiled with google translator that results in low-quality translation. This paper is aimed at comparing translation produced by Google Translate to translation produced by translator.